2020
DOI: 10.1002/stem.3194
|View full text |Cite
|
Sign up to set email alerts
|

Zinc transporter 3 modulates cell proliferation and neuronal differentiation in the adult hippocampus

Abstract: The subgranular zone of the dentate gyrus is a subregion of the hippocampus that has two uniquely defining features; it is one of the most active sites of adult neurogenesis as well as the location where the highest concentrations of synaptic zinc are found, the mossy fiber terminals. Therefore, we sought to investigate the idea that vesicular zinc plays a role as a modulator of hippocampal adult neurogenesis. Here, we used ZnT3 −/− mice, which are depleted of synaptic-vesicle zinc, to test the effect of targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…In addition, Zn functions as an important neuromodulator in the olfactory bulbs in rodents (240,241) . Restricting the release of Zn by knocking out the Zn exporter ZnT3 inhibited cell proliferation and neuronal differentiation in the adult hippocampus in mice (242) . Surprisingly, Zn in the brain remains unaltered or might even be elevated and involved in Alzheimer-related plaque formation in Zn-deficient animals and humans (243)(244)(245) .…”
Section: Zinc Deficiency As Pre-requisite To Virus-induced Neuronal Damage and Loss In Smell And Tastementioning
confidence: 99%
“…In addition, Zn functions as an important neuromodulator in the olfactory bulbs in rodents (240,241) . Restricting the release of Zn by knocking out the Zn exporter ZnT3 inhibited cell proliferation and neuronal differentiation in the adult hippocampus in mice (242) . Surprisingly, Zn in the brain remains unaltered or might even be elevated and involved in Alzheimer-related plaque formation in Zn-deficient animals and humans (243)(244)(245) .…”
Section: Zinc Deficiency As Pre-requisite To Virus-induced Neuronal Damage and Loss In Smell And Tastementioning
confidence: 99%
“…Our laboratory has demonstrated that synaptic zinc is an important factor for modulating hippocampal neurogenesis, and we used ZnT3 knockout mice to address this question. ZnT3 deficiency reduced progenitor cell proliferation and neuronal differentiation in the hippocampus, which was mediated by decreasing levels of IGF-1, ERK1/2 phosphorylation, and cyclic AMP response element binding protein (CREB) in the hippocampus of ZnT3 knockout mice at three months of age [ 70 ].…”
Section: Friendmentioning
confidence: 99%
“…In the pre-synaptic vesicles, chelatable zinc is abundant. It is released into the synaptic cleft, moved into pre-synaptic neurons via several transporters, and subsequently undergoes reuptake from the synaptic cleft under normal physiological conditions [ 22 , 23 ]. Under abnormal physiological conditions, such as neurological disorders, zinc homeostasis is disturbed and dysregulated.…”
Section: Introductionmentioning
confidence: 99%